Sustainable Procurement Maturity Model : Creation, Empirical Validation, and Utilization - Halonen, Tuomas (My University, 2020)
Sustainable procurement is a growing concern in organizations across industries, as stakeholders are placing higher emphasis on organization’s and its suppliers’ sustainability performance. Organization and its suppliers are not seen as separate entities regarding sustainability, and organizations are often held responsible for sustainability failures of their suppliers. Procurement has an imperative role driving forward organization’s sustainability, as it is placed between external and internal stakeholders and majority of sustainability implications arise from supply chain. Sustainable procurement builds commonly around triple bottom line (TBL) which integrates three dimensions; environmental, social, and economic. This study adopts the TBL concept. Even though sustainable procurement has gained popularity, and common frameworks such as TBL exists, the field has remained fragmented. Sustainable procurement is also a difficult task to implement in practice. Fragmentation, lack of knowledge, and difficulties regarding implementation and development are factors which can be eased through maturity models. There is a clear research gap as no empirically validated maturity model for sustainable procurement exists. The study uses a constructive research approach and creates the first empirically validated scientific maturity model for sustainable procurement and utilizes it. The model is based on existing scientific literature on procurement and sustainability, and the creation process follows frameworks presented in literature. Validation of the model is done through a questionnaire and an expert interview. The created model includes 38 dimensions that are grouped to five categories addressing common procurement tasks and enablers of sustainability. The study creates five levels of maturity evolving from “non-existent” to “sustainability leader”.The maturity model is tested with a questionnaire with a single organization and participants consist of procurement professionals. The organization received an overall maturity level of 2.47 out of 5. This maturity indicates that the organization has adopted a large variety of sustainable procurement practices, but they are not yet well implemented throughout the organization. Thus, there is a high dependency on individuals. The results also indicate that maturity of sustainability drivers and enablers, and supplier management are the lowest. Organization is also able to utilize the model as basis for future development. The maturity model should be more widely adopted to gain information on sustainable procurement in practice and generate generalizable results. This would provide valuable aid for both practitioners and scientific community.

Kestävän hankinnan merkitys organisaatioille on kasvussa sidosryhmien keskittyessä yhä enemmän organisaation sekä sen toimittajien kestävyyteen. Organisaatiota ja sen toimittajia ei enää nähdä erillisinä kokonaisuuksina, vaan organisaatiot joutuvat usein vastuuseen toimittajiensa vastuuttomasta toiminnasta. Hankinnalla on elintärkeä rooli organisaation kestävyyden kehittämisessä, sillä se sijaitsee ulkoisten ja sisäisten sidosryhmien välillä, ja suurin osa kestävyyteen vaikuttavista tekijöistä syntyy organisaation toimitusketjussa. Kestävä hankinta rakentuu yleisimmin kolmoistilinpäätöskäsitteen (TBL) ympärille, mikä koostuu kolmesta ulottuvuudesta; ympäristöllinen, sosiaalinen ja taloudellinen. Tämä tutkimus omaksuu TBL-käsitteen. Vaikka kestävä hankinta on kasvattanut suosiotaan ja yleisiä viitekehyksiä, kuten TBL, on olemassa, on aihealue edelleen hajanainen. Kestävän hankinnan toteuttaminen käytännössä on myös haastavaa. Hajanaisuus, tietotaidon puute, ja käytännön toteutuksen haasteet ovat asioita, joita voidaan parantaa maturiteettimallien avulla. Tämänhetkisessä tieteellisessä kirjallisuudessa on selkeä puute, sillä empiirisesti validoitua tieteellistä maturiteettimallia kestävälle hankinnalle ei ole kehitetty. Tämä tutkimus soveltaa konstruktiivista tutkimusotetta ja kehittää ensimmäisen empiirisesti validoidun tieteellisen maturiteettimallin kestävälle hankinnalle, sekä hyödyntää sitä käytännössä. Malli perustuu tieteelliseen kirjallisuuteen hankinnasta sekä kestävyydestä, ja sen kehitysprosessi seuraa kirjallisuudessa esitettyjä viitekehyksiä. Mallin validointi suoritetaan kyselyn ja asiantuntijahaastattelun avulla. Kehitetty malli sisältää 38 dimensiota, jotka luokitellaan viiteen hankinnan tehtäviä ja kestävyyden mahdollistajia kuvaavaan kategoriaan. Tutkimuksessa luodaan viisi maturiteettitasoa, jotka kehittyvät ”olemattomasta” ”kestävyysjohtajaan”. Mallia hyödynnetään kyselynä yhden organisaation kanssa, ja osallistujat ovat hankinnan ammattilaisia. Organisaatio sai tietoonsa yleisen maturiteettitason, joka oli 2.47 ylimmän tason ollessa 5. Tämä taso indikoi, että organisaatio on implementoinut suuren joukon kestävän hankinnan käytäntöjä, mutta ne eivät ole vielä samalla tasolla läpi organisaation. Toteutus on vielä hyvin paljon kiinni yksiöistä. Tuloksien mukaan heikoin maturiteettitaso on ryhmillä kestävän hankinnan ajurit ja mahdollistajat, sekä toimittajahallinta. Organisaatio käytti mallia myös tulevan kehityksen pohjana. Kehitettyä maturiteettimallia tulisi hyödyntää laaja-alaisemmin, jotta voitaisiin saada yleistettäviä tuloksia sekä paremmin ymmärtää kestävää hankintaa käytännön tasolla. Tämä hyödyttäisi sekä organisaatioita, että tieteellistä yhteisöä.
Keywords: Sustainable procurement, Maturity model